2018
DOI: 10.1111/nan.12520
|View full text |Cite
|
Sign up to set email alerts
|

Invited Review: From nose to gut – the role of the microbiome in neurological disease

Abstract: Inflammation and neurodegeneration are key features of many chronic neurological diseases, yet the causative mechanisms underlying these processes are poorly understood. There has been mounting interest in the role of the human microbiome in modulating the inflammatory milieu of the central nervous system (CNS) in health and disease. To date, most research has focussed on a gut‐brain axis, with other mucosal surfaces being relatively neglected. We herein take the novel approach of comprehensively reviewing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 152 publications
(192 reference statements)
0
69
0
Order By: Relevance
“…An emerging theme in studies of various NDDs is the role of peripherally initiated dysfunction that propagates centrally to promote cerebral pathology [18][19][20][21][22]45,46] Here, we showed the presence of dysregulation of IEB and intestinal absorption as well as increased inflammatory and angiogenic plasma cytokines prior to development of cerebral Aβ accumulation in Tg2576 mouse model of AD. Our findings support the notion that Aβ-induced vascular injury may begin in the intestinal vasculature and lead to loss of IEB integrity as assessed by a reduction in mucus and E-cadherin…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…An emerging theme in studies of various NDDs is the role of peripherally initiated dysfunction that propagates centrally to promote cerebral pathology [18][19][20][21][22]45,46] Here, we showed the presence of dysregulation of IEB and intestinal absorption as well as increased inflammatory and angiogenic plasma cytokines prior to development of cerebral Aβ accumulation in Tg2576 mouse model of AD. Our findings support the notion that Aβ-induced vascular injury may begin in the intestinal vasculature and lead to loss of IEB integrity as assessed by a reduction in mucus and E-cadherin…”
Section: Discussionmentioning
confidence: 70%
“…The regulatory role of the gut-brain axis in NDDs is increasingly being recognized [18,19]. In 2011, using microbiota transplants, Bercik et al showed that strain-specific behavioral traits in mice can be transmitted along with the microbiota [20] and Heijtz et al showed that germ-free mice exhibit a less-anxious behavioral phenotype than conventionally raised mice [7].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the gut microbial compositions or microbial dysbiosis, is defined as a decrease in the intestinal microbial diversity resulting in an imbalance between commensal "protective" versus potential pathogens "harmful", thus promoting an excessive intestinal inflammation [52]. When persistent, this response can induce a chronic, unregulated intestinal inflammation that is observed in various human diseases such as IBD, irritable bowel syndrome, asthma, obesity, cardiovascular diseases, kidney diseases, to name a few, from the wide array of diseases known to present with gut dysbiosis [39,41,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72].…”
Section: Microbiomics In Ibd: From Postulated Theories To Known Diffementioning
confidence: 99%
“…There are also lots of studies presenting that PD is tightly connected with environment factors, and microbiota is considered as an important pathogen for PD [23]. There has been mounting interest in the role of human microbiome in modulating the in ammatory milieu of the central nervous system in PD [24]. Some environmental factors, such as caffeine consumption and cigarette smoking, may alter the composition of the microbiome in the gut in a way in uencing the in ammation of intestine [25].…”
Section: Discussionmentioning
confidence: 99%